The Role of Attachment Trauma and Disintegrative Pathogenic Processes in the Traumatic-Dissociative Dimension - Benedetto Farina; Benedetto Farina; Marianna Liotti; Claudio Imperatori (Frontiers in Psychology, 2019)
Epidemiological, clinical, and neurobiological studies of the last 30 years suggest that traumatic attachments during the early years of life are associated to specific psychopathological vulnerabilities based on dissociative pathogenic processes. It has been observed that the dissociative pathogenic processes caused by these traumatic attachments either may contribute to the genesis of well-defined mental disorders (e.g., dissociative disorders) or may variably occur in many other diagnostic categories, complicating their clinical pictures and worsening their prognosis. For this reason, we proposed to define the dimension of psychopathological outcomes linked to traumatic attachments and dissociative pathogenic processes as the “traumatic-dissociative” dimension (TDD). The clinical complexity of the TDD requires specific training to enable mental health professionals to recognize the signs of traumatic developments and to implement specific treatment strategies. The present article aims to review some crucial points about the clinical meaning and treatment strategies of the TDD, the dissociative pathogenic processes characterizing the TDD, as well as of the role of attachment trauma in the TDD. We also focused on the clinical and theoretical evidence suggesting that dissociation and dis-integration may be considered two different processes but highly correlated. The usefulness of clinical reasoning in terms of psychopathological dimensions, instead of distinct diagnostic categories, as well as several therapeutic implications of these issues was finally discussed.